Land Suitability Re-evaluation for Fruit Crops in the Post-Eruption Merapi 2010 - Aini, L. N. (IOP Publishing Ltd, 2022)
The Mt. Merapi eruption in 2010 devastated the economic and ecological conditions in the affected areas. However, the volcanic material from the eruption has a positive impact on land rejuvenation, due to the addition of weatherable minerals which are rich in nutrients for plants. This study aims to re-evaluate the land suitability of the areas affected by the 2010 Merapi eruption for fruit crops. The research was conducted at 7 areas (Kaliadem, Kinahrejo, Jambu, Petung, Ngepringan, Pager Jurang, and Gadingan) based on the volcanic material distribution map. The selected commodities and will be developed are based on the existence of fruits that grew in this area before the eruption, namely jackfruit, avocado, banana, and arabica coffee. The results of this study indicate that land that has been affected by the Merapi eruption is classified as unsuitable for the proposed commodity with the main limiting factor being low nutrient and water retention, in addition to the upper slope area there are additional slope limiting factors. However, this area still has the opportunity to be developed because it is rich in "weatherable minerals"which can be a source of nutrients for plants. Amendment materials that can increase nutrient and water retention and accelerate the release of nutrients from rocks need to be provided, such as compost rich in organic acids. © Published under licence by IOP Publishing Ltd.